Techno-economic optimization and cycle schedule analysis of poly-bed VPSA process for CO2 capture from natural gas combustion emissions using parallel Bayesian optimization with ANN ensembles - Jun Woo Park; Gyubin Sim; Ki Bong Lee (Chemical Engineering Journal, 2026)

Exposure to traffic-related air pollution and the risk of premature rupture of membranes: a cohort analysis of the Korean CHildren’s ENvironmental health Study (Ko-CHENS) - Dong-Wook Lee; Kyung A. Lee; Jongmin Oh; Hwan-Cheol Kim; Sanghwan Song; Yun-Chul Hong; Eunhee Ha; Suejin Kim; Choonghee Park; Sanghwan Song; Jueun Lee; Huibyeol Park; et al. (Environmental Science and Pollution Research, 2026)

Prediction and application on the first flowering date of June-bearing strawberry cultivars using Ensemble-based Machine learning with primary temperature values - Tae Yeon Lee; Yu Hyun Moon; Ha Seon Sim; Soo Bin Jung; Ui Jeong Woo; Ha Rang Shin; Yong Jun Kim; Na Kyoung Kim; Jung Su Jo; Sung Kyeom Kim (Computers and Electronics in Agriculture, 2026)

Associations of pre- and postnatal levels of three heavy metals with visual impairment in 3-year-old children - Dajeong Ham; Sung Yeon Kim; Sanghyuk Bae; Suejin Kim; Choonghee Park; Sanghwan Song; Jueun Lee; Huibyeol Park; JungHeum Jo; A-Ra Jung; Seung Do Yu; Hyun Jeong Kim; et al. (Environmental Research, 2025)

Bioprinting of cardiac patches with gold-nanowires and tri-culture system for the treatment of myocardial infarction - WonJin Kim; Jung Won Yoon; Woo-Sup Sim; Ye Seul Kim; SooJung Chae; Byungjoon Choi; Hun-Jun Park; Jae Ho Kim; GeunHyung Kim (Chemical Engineering Journal, 2025)

TRPA1 nanovesicle-conjugated receptonics for rapid biocide screening - Kyung Ho Kim; Jisung Kwak; Sung Eun Seo; Siyoung Ha; Gyeong-Ji Kim; Sangwoo Lee; Sang Jun Sim; Yeon Kyung Lee; Na Ly Tran; Seung Ja Oh; Woo-Keun Kim; Hyun Seok Song; et al. (Journal of Hazardous Materials, 2024)

Correction to: Prediction of strawberry fruit yield based on cultivar-specific growth models in the tunnel-type greenhouse - Jung Su Jo; Dong Sub Kim; Won Jun Jo; Ha Seon Sim; Hye Jin Lee; Yu Hyun Moon; Ui Jeong Woo; Soo Bin Jung; Steven Kim; Xiaoming Mo; Su Ran Ahn; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2023)

Prediction of strawberry fruit yield based on cultivar-specific growth models in the tunnel-type greenhouse - Jung Su Jo; Dong Sub Kim; Won Jun Jo; Ha Seon Sim; Hye Jin Lee; Yu Hyun Moon; Ui Jeong Woo; Soo Bin Jung; Steven Kim; Xiaoming Mo; Su Ran Ahn; Sung Kyeom Kim (Horticulture, Environment, and Biotechnology, 2022)
The strawberry growth and fruit yield of five Korean cultivars in the tunnel-type greenhouse predicted using their growth. The number of leaves, petiole length, leaf length and width, crown diameter, and the ratio of red and far-red (RFR) of the five Korean cultivars were measured during the cultivation period. The number of leaves of all cultivars exhibited a similar trend during this period; the plant and petiole length of ‘Maehyang’ were the longest, leaf length exhibited similar trends in all five cultivars except for ‘Jukhyang’, the leaf width of ‘Arihyang’, was the longest, and crown diameter of ‘Keumsil’ was the thickest. The leaf length, crown diameter, and RFR were associated with the fruit yield in the multiple linear regression. When a single model was used to predict the yield of all five cultivars, the correlation between expected yield and actual yield was r = 0.53. When cultivar-specific models were built for the prediction, the correlation increased to r = 0.77. The results indicated that the fruit yield of strawberry cultivars could be better predicted by considering cultivar-specific information, so it may be necessary to consider individual cultivars specifically rather than all cultivars simultaneously.

Physiochemical Changes in Lipid-rich Mackerel during the Preparation of Smoked Mold Ripened Meat Products - Joon-Young Jun; Min-Jeong Jung; Jun-Seok Kum; Gwang-Woo Kim; Jae-Hyung Jung; Jae-Man Sim; In-Hak Jeong; Byoung-Mok Kim (Journal of Aquatic Food Product Technology, 2020)

Cardiac adaptation to exercise training in health and disease - Dae Yun Seo; Hyo-Bum Kwak; Amy Hyein Kim; Se Hwan Park; Jun Won Heo; Hyoung Kyu Kim; Jeong Rim Ko; Sam Jun Lee; Hyun Seok Bang; Jun Woo Sim; Min Kim; Jin Han (Pflügers Archiv - European Journal of Physiology, 2020)

Hydrocarbon production from secondarily treated piggery wastewater by the green alga Botryococcus braunii - Jin-Young An; Sang-Jun Sim; Jin Suk Lee; Byung Woo Kim (Journal of Applied Phycology, 2003)

Increased poly-β-hydroxybutyrate (PHB) chain length by the modulation of PHA synthase activity in recombinant Escherichia coli - Sang Jun Sim; Kristi D. Snell; Byung Woo Kim; Cho Kyun Rha; Anthony J. Sinskey (Biotechnology Letters, 2001)

Two-phase extraction culture of Botryococcus braunii producing long-chain unsaturated hydrocarbons - Sang-Jun Sim; Jin-Young An; Byung-Woo Kim (Biotechnology Letters, 2001)